A study on issues and challenges of tour operators in Kota Kinabalu capital city of Sabah / Ammenuel Rimin - Rimin, Ammenuel (2011)
Tourism is one of the largest and fastest growing global industries, creating significant employment and economic development, particularly in many developing countries. Tour operators are an important part of this growth. Tour operators are businesses that combine two or more travel services, for example transport, accommodation, meals, entertainment and sightseeing. They then sell them through travel agencies or directly to final consumers as a single product which is called as package tour for a global price. The components of a package tour might be pre-established or can result from an "a la carte" procedure, in which the visitor decides the combination of services he or she wishes to acquire. The most common example of a tour operator's product would be a flight on a charter airline plus a transfer from the airport to a hotel and the services of a local representative, all for one price. As for travel agency, it is a business that is designed to help customers make various types of arrangements for trips such as tickets and hotel reservations. Thus, unlike the travel agencies who sell holiday and a range of other travel products, tour operators actually assemble the component parts of a holiday into package holidays. If we consider that the travel agents are the retailer arm of the travel business, then the tour operators can be linked to wholesalers, since they buy in 'bulk' from the providers of travel services, such as the hoteliers and airlines, break the 'bulk' into manageable packages and offer the finished product the inclusive tour for sale to the travel agencies or direct to the consumer. As intermediaries between tourists and tourism service providers, tour operators can influence the choices of consumers. This unique role means that tour operators can make an important contribution to furthering the goals of sustainable tourism development and protecting the environmental and cultural resources on which the tourism industry depends for its survival and growth.